Composite nationalism and Islam = Muttahida qaumiyat aur Islam - Madni, Sayyid Husain Ahmad, 1878-1957; Hussain, Mohammad Anwer; Imam, Hasan (New Delhi : Manohar, 2005)
With reference to India
Keywords: Nationalism -- Religious aspects -- India; Muslims -- India